2021
DOI: 10.1136/bmjopen-2020-039745
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of cold spells on hospitalisations for acute exacerbation of chronic obstructive pulmonary disease: a time-series study in Beijing, China

Abstract: ObjectivesOur work aimed at exploring the relationship between cold spells and acute exacerbation of chronic obstructive pulmonary disease (AECOPD) hospitalisations in Beijing, China, and assessing the moderating effects of the intensities and the durations of cold spells, as well as identifying the vulnerable.DesignA time-series study.SettingWe obtained time-series data of AECOPD hospitalisations, meteorological variables and air quality index in Beijing, China during 2012–2016.ParticipantsAll AECOPD hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…7,12,15,45 When exposed to cold temperature or air pollution, the airway epithelium is irritated, which causes the body to respond with coughing, bronchoconstriction, and mucosal secretion. 1,46 Cold stress and PM 2.5 experiments in adulthood of mice showed that coexposure may promote the deterioration of asthma symptoms by increasing inflammatory cytokines, ROS formation, Th2/Th1 imbalance, and suppressing the differentiation of Th17 toward Treg cells. 47,48 Further deaths from respiratory disease will occur in sensitive individuals (e.g., elderly people, etc.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,12,15,45 When exposed to cold temperature or air pollution, the airway epithelium is irritated, which causes the body to respond with coughing, bronchoconstriction, and mucosal secretion. 1,46 Cold stress and PM 2.5 experiments in adulthood of mice showed that coexposure may promote the deterioration of asthma symptoms by increasing inflammatory cytokines, ROS formation, Th2/Th1 imbalance, and suppressing the differentiation of Th17 toward Treg cells. 47,48 Further deaths from respiratory disease will occur in sensitive individuals (e.g., elderly people, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is a need for a warning system with local characteristics. According to the Q-AIC, the best definition of all-cause mortality was P2T4, the threshold of which was the same as cold spell research in China processed by Chen et al, , and the air pollution research processed by Zhang et al ,,, However, the combined event defined by P1T5 showed the highest cumulative relative risk, which means that an early warning should be triggered on the first exposure day when the temperature is lower than the 2.5th percentile and lasts for at least 48 h. The stricter definition showed a higher relative risk, but the protective ability was quite limited. The loose definition could capture more exposure events with wider protection, though its relative risk was relatively lower .…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the research of Liang et al, that is, the optimal cold wave was defined as temperature threshold ≤P 5 and duration ≥2 days ( 4 ). However, Liu et al found that the optimal cold wave was defined as the days with temperature threshold ≤P 10 and duration ≥4 days for COPD hospitalized population in Beijing ( 7 ). This suggested that different definitions may apply to different regions, climates, and health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…( 1 ): where Z denotes the Z-test; E 1 and E 2 are the effect estimates (i.e. ln (RR)) of two subgroups; SE (E 1 ) and SE (E 2 ) are corresponding Standard Errors of E 1 and E 2 45 .…”
Section: Methodsmentioning
confidence: 99%